2006
DOI: 10.7790/ejap.v2i1.32
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and Knowledge about Parkinson’s Disease

Abstract: A survey of public attitudes showed that there is significant stigma perceived to be associated with Parkinson's disease (PD), as well as significant misconceptions about the course and outcomes of the disease. Negative attitudes to PD were associated with perceived stigma, (younger) age, knowledge of a sufferer and knowledge of the disease. Perceived stigma, negative attitudes and incorrect beliefs are likely to impinge on the psychosocial well-being of those living with the disease, particularly those with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 16 publications
4
43
0
Order By: Relevance
“…One telephone survey conducted among Australian households asked similar questions related to PD causes, symptoms, diagnosis and management with an average of 66% of items answered correctly (Moore & Knowles 2006). Those study participants were younger than those in our sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One telephone survey conducted among Australian households asked similar questions related to PD causes, symptoms, diagnosis and management with an average of 66% of items answered correctly (Moore & Knowles 2006). Those study participants were younger than those in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of Alzheimer’s disease, higher levels of knowledge about the disease were associated with greater help-seeking behavior (Werner 2003). Prior studies of PD knowledge and attitudes in the community have shown that reported knowledge of PD is low (Werner & Korczyn 2010), and many associate stigma with the disease (Moore & Knowles 2006). These may act as additional barriers to care, particularly for underserved minorities.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative research also has validated the source of stigma by surveying public attitudes toward PD [9] and by examining others’ impressions of PD symptoms [10-12]. Moore and Knowles reported that nearly half of survey respondents considered the disease to be stigmatizing [9].…”
Section: Introductionmentioning
confidence: 99%
“…Socioeconomic status is a crucial factor to consider when developing public educational programs about PD. Many studies have reported a lack of knowledge and/or misconceptions about PD among diverse older populations, such as different community-based groups or racial/ethnic groups [6,[11][12][13]19] . However, in our study, differences in the awareness and knowledge about PD were not significant when comparing rural and urban areas.…”
Section: Categorymentioning
confidence: 99%
“…Therefore, awareness and knowledge about PD among the general population is crucial for early diagnosis and optimal management of the disease. There have been some survey studies assessing the knowledge of PD in specific regional groups or in diverse groups of elderly patients, and generally, these studies have found a low level of knowledge about PD among those surveyed [6,[11][12][13] . In 2009, the European Parkinson's Disease Association (EPDA) conducted a survey about the perception of PD across Europe [14] .…”
Section: Introductionmentioning
confidence: 99%